032. Infective Endocarditis with Right Atrium Vegetative Due to Infection of Catheter Double Lumen: A Case Report - Riendra, Muhammad; Rahman, Aulia; Ardiansyah, Ardiansyah; Jayanti, Ranti (JBN (Jurnal Bedah Nasional), 2024)
Background : Infective endocarditis (IE) associated with Catheter Double Lumen (CDL) is uncommon. This condition is masked by suspicion of common CDL infection which is treated with CDL replacement. CDL-related IE in chronic kidney disease (CKD) patients who routinely undergo hemodialysis is a condition that requires integrated management among multi-disciplines, especially in children patient. Until now, open heart surgery with cardiopulmonary bypass is still the standard procedure for vegetation evacuation in IE. Endovascular modality is a challenging intervention because of the risk of pulmonary embolism due to the detachment of vegetation. Case : We report a case of a 13-year-old girl with a history of repeated CDL placement who came to the emergency room with high fever since 2 weeks before admission. The patient is known as CKD with a history of the last CDL placement 4 months ago. Yellowish fluid with positive pus came out of the catheter site. Echocardiography showed a 2.5 cm right atrial vegetation surrounding the CDL and had protruded into the tricuspid valve and right ventricle.  After IE management, the vegetation was still large and we decided to evacuated the vegetation. There were no difficulties or complications either intraoperatively or postoperatively and the patient was discharged with good results. Conclusion: Infection in CDL should be suspected as endocarditis until proven otherwise because it will affect the management and surgical intervention required.